Analisis Kinerja Keuangan Bank Umum Swasta Nasional Sebelum dan Sesudah Akuisisi - Usman, Umedi (Universitas Brawijaya, Indonesia, 2013)
The research aimed at determining: 1) whether acquisition had a positive impact on the financial performance of bank; and 2) what ratio of contribution the variable of liquidity, solvability, rentability and efficiency play in the financial performance of bank. The research result shows that: (1) Of the 4 financial ratio under investigation, two financial ratios, i.e. LDR and BO/PO grew better however not significant, and one ratio, i.e. solvability (EM) was still in good condition, and another ratio, i.e. rentability (ROA and ROE) increasingly declined. Based on the rentability ratio, it is concluded that the acquisition activity failed to gain the optimal advantage due to distortion of the strong external factor, i.e. the economy crisis. (2) The liquidity ratio had dominant influence on the financial performance of the bank. Although acquisition did not achieve optimal result, it is hoped that the economic condition recovery yields positive impact on the financial performance of banks. Therefore, it is suggested that acquisition be continuously applied by banks that are still in need of fund in order to become healthy.